The Role of Atmosphere in Electric Current: How Air Pressure and Composition Affect Conductivity (Eurasian Journal of Engineering and Technology, 2023)
Electric current is the flow of charged particles through a conductor. Atmosphere plays a significant role in electric current as the air pressure and composition affect conductivity. The air pressure affects the dielectric strength of the air, which determines how much voltage can be applied before a breakdown occurs. The composition of the air affects the number of free electrons available for conduction. In this article, the effects of atmospheric pressure and composition on electric current are discussed. Results from experiments conducted in Uzbekistan reveal that increasing air pressure increases the breakdown voltage, while increasing the oxygen concentration enhances the conductivity of the air.